12 Sex differences in the agreement between left ventricular ejection fraction measured by myocardial perfusion scintigraphy and by echocardiography. (May 2019) - Han, Thang; Moosai, Kishan; Jaker, Sams; Burgan, Amjad; Jacques, Adam; Fluck, David; MacGregor, Mark; Lazariashvili, Otar; Prakash, Vineet; Sharma, Pankaj; Fry, Christopher
Abstract : Background: Left ventricular ejection fraction (LVEF) is generally measured by echocardiography (Echo) but is increasingly available with myocardial perfusion scintigraphy (MPS). With MPS the threshold of LVEF below which there is a risk for myocardial infarct or sudden cardiac death is higher for women (51%) than for men (43%) [Shahir T, et al . J Nucl Cardiol 2006;13:495–506]. We tested the hypothesis that such a sex difference may also occur with Echo and MPS, by comparing LVEF measured by both methods. Participants and setting: A total of 1141 patients underwent cardiac assessment, including resting LVEF measured both by MPS and Echo. Of these 743 patients (404 men, mean age=67.7±SD=12.3 yr; 339 women, 67.7±11.7 yr) had separate examinations within 6months and their data used for analysis. A subset of 327 of these patients (181 men, 68.8±12.1 yr; 146 women, 66.4±12.1 yr) had examinations at a shorter time apart (within 1month) and were additionally analysed as this sub-group. All examinations were at Ashford & St Peter's NHS Foundation Trust between 30–11–2012 and 30–05–2017 (figure 1 ). Methods: The rest MPS was performed with the injection of 99mTc-tetrofosmin (600–1000MBq). Images were obtained using dual-head SPECT cameras (Siemens Symbia S, Erlangen, Germany) and LVEF was determined from gated images. The rest Echo was performed with a high-end 2-dimensional echocardiographic unit (Sonos 5500, Andover, Mass., US or Vingmed System V, Horten, Norway) and images were acquired with standard parasternal, short-axis and apical views and LVEF was calculated by the modified Simpson's biplane disks method. Agreement between MPS and Echo (neither considered as a reference method) was assessed by Bland-Altman plots: LVEF difference (MPS minus Echo) against average LVEF ((MPS+Echo)/2). Data are presented as means and ±SD. Results: Of patients who had MPS and Echo examinations within 6months, mean LVEF difference was +1.1% (95% limits of agreement (±2SD)=-19.3 to +21.6) in men (figure 2a) but +10.9% (-10.7 to +32.5) in women (figure 2b). A one-tailed t-test showed LVEF difference diverged from zero only marginally in men (mean difference=+1.1, 95%CI=+0.1 to +2.1, p=0.028) but more in women (+10.9, +9.8 to +12.1, p<0.001). The LVEF difference correlated significantly with average LVEF itself in both men (r=0.305, p<0.001) and women (r=0.361, p<0.001), and with age in women (r=0.117, p=0.031). Similar results were observed for the subset (MPS and Echo performed within 1month apart): LVEF difference was +1.3% (-18.1 to +20.7) in men and +11.3% (-10.6 to +33.2) in women. The LVEF difference again correlated significantly with average LVEF in men (r=0.361, p<0.001) and women (r=0.392, p<0.001), but not with age in either sex. Conclusion: Caution should be taken when interpreting LVEF measured by different techniques due to their wide limits of agreement and systematic bias, more markedly in women. Our data however cannot provide an underlying explanation for these differences but physiological and anatomical differences between men and women may contribute, e.g. cardiac morphology, haemodynamics and body habitus. Conflict of Interest: None